OFF TV PROGRAM IMPLEMENTATION TO PROMOTE CHILDREN’S LEARNING MOTIVATION AT SUKOANYAR CERME GRESIK - Muyasaroh m; Hadiyatan Wasilah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Muhammadiyah Gresik, 2017)
The background of the study is the OFF TV program at study hours, at 18.00 to 20.00 p.m at Sukoanyar Cerme Gresik. The study is oriented on describing the implemented OFF TV program. It also describes the effect of OFF TV program to promote children’s learning motivation. This study employs descriptive qualitative method. The data were collected through observation, interview, and documentation to dig information about the implementation of the OFF TV program and its effect on promoting children’s learning motivation. The object of the study is the OFF TV program, while the subject involves Sukoanyar residents who are currently studying in junior high school, and parents as the research data refinement. The data was analyzed using Miles and Huberman model, while triangulation technique and member check were used to test the validity. The result of the study showed that the OFF TV program implementation from 18.00 to 20.00 p.m can be applied all day to all residents in Sukoanyar village regulated by the Village Regulation No. 02 year 2016 with the aim of improving the human resources quality in Sukoanyar village. The result also showed the effect of the OFF TV program on promoting children’s learning motivation with some indicators. The first indicator is children feel happy with the OFF TV program because of the conducive environment for learning, the second indicator is they are more discipline in learning because there is special time to learning, the third is children can concentrate in learning, the fourth is they can study diligently, do their work freely without any interruption that can make them more serious and never give up.